The Meaning of the Word Al Mishbah in the Qur’an with Toshihiko Izutsu Semantic Analysis - Dini Rona Ayuni; Kharis Nugroho; Andri Nirwana AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study examines the meaning of the term